2010
DOI: 10.1016/j.outlook.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A thematic analysis of theoretical models for translational science in nursing: Mapping the field

Abstract: Background The quantity and diversity of conceptual models in translational science may complicate rather than advance the use of theory. Purpose This paper offers a comparative thematic analysis of the models available to inform knowledge development, transfer, and utilization. Method Literature searches identified 47 models for knowledge translation. Four thematic areas emerged: (1) evidence-based practice and knowledge transformation processes; (2) strategic change to promote adoption of new knowledge; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 134 publications
3
113
0
Order By: Relevance
“…Evidence from a variety of fields, including public health, have found that interventions using health behavior theories are more effective than those lacking a basis in theory, as a theory-based model can provide a way to guide the search for evidence on interventions needed in the process of change in the intermediate variables (such as behavior) leading to the health outcome (69, 80, 139). A theory is a set of interrelated concepts, definitions, and propositions that present a systematic view of events by specifying relations among variables, in order to explain and predict events (70), and to impute potential interventions for which evidence can be sought (87).…”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
“…Evidence from a variety of fields, including public health, have found that interventions using health behavior theories are more effective than those lacking a basis in theory, as a theory-based model can provide a way to guide the search for evidence on interventions needed in the process of change in the intermediate variables (such as behavior) leading to the health outcome (69, 80, 139). A theory is a set of interrelated concepts, definitions, and propositions that present a systematic view of events by specifying relations among variables, in order to explain and predict events (70), and to impute potential interventions for which evidence can be sought (87).…”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
“…Perceptions of risk and uncertainty are important for the acceptance or rejection of new food technologies (Ronteltap et al, 2007). The perception of an innovation as low risk has previously been shown to increase pre-adoption of novel technology in allied health professions (Mitchell et al, 2010;Greenhalgh et al, 2004).…”
Section: Science Versus Pseudosciencementioning
confidence: 99%
“…This view is consistent with recent calls for a more integrative and functional approach to the dietetic curriculum (Augustine et al, 2016). Incorporation of novel technology into curricula has been positively associated with adoption of new innovations among various professions (Aarons et al, 2011;Mitchell et al, 2010; Greenhalgh et al, 2004).Participants believed that nutritional genomics should be part of the undergraduate core There were also concerns that not enough emphasis was placed on the relevance of nutritional genomics to dietetics practice, which could be more extensively covered in the curriculum. …”
mentioning
confidence: 99%
“…4 Although there are many EBP and translational science models and frameworks, there are few models that map out the decision-making process for understanding when QI and EBP projects become research and require protections for human subjects, including informed consent. 5 …”
Section: Blurred Linesmentioning
confidence: 99%